Retail Business Strategy In Increasing Sales Through Innovation And Customer Experience - Ayu Lestari; Hanum Agnia (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2023)
In retail, strategies in increasing sales through innovation and customer experience can be a critical factor in business success. In this case, artificial intelligence can be used to analyze customer data and market trends to develop innovations and customer experiences that can increase sales. To achieve this goal, it is necessary to implement an effective data management strategy and the use of appropriate technology to collect and analyze customer data in real-time. Thus, retail businesses can understand customer behavior, and design innovations that suit their needs. In addition, artificial intelligence can help retail businesses in the development of effective and relevant marketing strategies, leading to increased customer traction and experience. Through data analysis, retail businesses can identify market trends and customer needs, and develop innovative solutions that can improve customer experience. In addition, artificial intelligence can help retail businesses in developing effective and relevant marketing strategies, leading to increased customer attraction and experience.